Faktor yang Mempengaruhi Perilaku Gizi Seimbang Pada Siswa Di SMA Negeri 1 Muara Beliti - Putri, Tita Priyanka; Yuliarti, Yuliarti (Indonesian Journal of Nutrition Science and Food; Vol 2 No 1 (2022): Juni 2022, 2022)
Unhealthy eating patterns in today's adolescents, occur due to lack of nutritional knowledge as a result of the delivery of health information that is given incorrectly and incorrectly. This study aims to see at related factors with balanced nutrition behavior in SMA Negeri 1 Muara Beliti. This research is analytic observational with cross sectional approach. Sample collection was done by simple random sampling technique. The sample in this study was 88 students of SMA Negeri 1 Muara Beliti with grades 10, 11, 12. Data collection was taken using independent questionnaires. This research uses univariate and bivariate analysis with chi square test. The results of the frequency distribution of 88 respondents on the balanced nutrition behavior, most of the respondents had poor behavior, of 49 (55,7%) respondents. The results of the bivariate analysis showed that there was a relationship between mass media exposure (p = 0.11) with balanced nutrition behavior and there was no relationship between knowledge of balanced nutrition (p = 0.719), pocket money (p = 0.290), parents' income (p = 1 ), residence (p = 0.177) with balanced nutritional behavior. Researchers suggest that schools can provide education to their students about balanced nutrition through pamphlets, banners and posters so that because there are still many students who have less knowledge about balanced nutrition.